CTNI-19. CONCURRENT CHEMORADIATION AND TUMOR TREATING FIELDS (TTFields, 200 kHz) FOR PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA MAY INCREASE THE RATE OF DISTANT RECURRENCE. (12th November 2021) - Ali, Ayesha S; Niazi, Muneeb; Bar-Ad, Voichita; Werner-Wasik, Maria; Andrews, David; Farrell, Christopher; Evans, James; Judy, Kevin; Glass, Jon; Nina, L Martinez; Alnahhas, Iyad; Chervoneva, Inna; et al.
Abstract: INTRODUCTION: Current standard of care for glioblastoma (GBM) includes concurrent chemoradiation and maintenance temozolomide (TMZ) along with Tumor Treating Fields (TTFields). Preclinical studies suggest TTFields and radiation treatment have synergistic effects. Secondary analysis of EF14 trial demonstrated TTFields treatment may increase the rate of distant recurrence. We report our experience evaluating areas of progression in our pilot clinical trial of concurrent chemoradiation with TTFields. METHODS: This is a single arm pilot study (clinicaltrials.gov Identifier: NCT03477110). Adult patients (age ≥ 18 years) with KPS ≥ 60 with newly diagnosed GBM were eligible. All patients received concurrent scalp-sparing radiation (60 Gy in 30 fractions), standard concurrent TMZ (75 mg/m2 daily), and TTFields. Maintenance therapy included standard TMZ and continuation of TTFields. Radiation treatment was delivered through TTFields arrays. Incidence and location of progression was documented. Distant recurrence was defined as recurrence more than 2 cm from primary enhancing lesion. RESULTS: A total of 30 patients were enrolled on the trial. Twenty were male, and ten were female, with median age 58 years (19-77 years). Median KPS was 90 (70-100). Median follow-up was 11.6 months (1.7-22.1 months). Twenty (66.7%) patients had an unmethylated MGMT promotor status and ten (33.3%) patients had a methylated promoter status. Twenty patients (66.7%) had progression, with median PFS of 9.1 months (range 1.6 to 12.9 months). Five patients (26%) of patient presented with distant recurrence, with median distance from primary lesion of 5.1 cm (2.26-9.12 cm). One infratentorial progression was noted. Another patient transferred care and location of progression is unknown. CONCLUSIONS: Concurrent chemoradiation with TTFields for patients with newly diagnosed glioblastoma may have increased incidence of distant recurrence. This finding is suggestive of improved local control of primary site. Further data are needed to validate this finding.